2019
DOI: 10.1111/jonm.12862
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of the physical health care environment on nurse fatigue

Abstract: Aim(s) The purpose of this study was to investigate factors in the physical health care environment (PHE) contributing to nurse fatigue. Background Nurses experience high levels of physical, mental and overall fatigue related to the physically demanding and mentally complex nature of bedside care. Method(s) This study used secondary data analysis of a 2017 focus group session, which explored: (a) challenges nursing professionals face while delivering care, (b) the effect of nurse fatigue on care delivery and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Surveys revealed that staff members' ability to surveil patients and to see each other had significant effects on staff satisfaction (Zamani, 2019). Similarly, Wingler and Keys (2019) reported that peer-to-peer visibility and visual connection to the patients within the unit are design dimensions that affect both cognitive and psychosocial fatigue.…”
Section: Design Of Intangible Elements and Staff Health Outcomesmentioning
confidence: 99%
“…Surveys revealed that staff members' ability to surveil patients and to see each other had significant effects on staff satisfaction (Zamani, 2019). Similarly, Wingler and Keys (2019) reported that peer-to-peer visibility and visual connection to the patients within the unit are design dimensions that affect both cognitive and psychosocial fatigue.…”
Section: Design Of Intangible Elements and Staff Health Outcomesmentioning
confidence: 99%
“…7 Research has focused on the fatigue problem faced by nurses, with the goal of developing evidence-based fatigue management strategies and indicators to improve nurses’ sense of satisfaction at work and the quality of nursing services. 8 9 …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to impair a nurse’s ability to work, putting patients at risk of getting their medication at the wrong time and dose 7. Research has focused on the fatigue problem faced by nurses, with the goal of developing evidence-based fatigue management strategies and indicators to improve nurses’ sense of satisfaction at work and the quality of nursing services 8 9…”
Section: Introductionmentioning
confidence: 99%
“…Nurses undergoing high levels of occupational stress face many problems under the risk of physical, psychological, and behavioral stress. These problems are ergonomically unfavorable working environments, task complexity, time pressure, use of intensive technology, working in shifts, frequent encounters with death, excessive workload, insomnia, fatigue, tension, exhaustion, anxiety, helplessness, and so forth (Bülbüloğlu et al, 2021; Özdaş & Kızılkaya, 2021; Samhat et al, 2020; Wingler & Keys, 2019). Since this occupational stress experienced by nurses has recently reached quite alarming levels, it is an issue on which scientists are focusing a lot today (Alkhawaldeh et al, 2020; Dehdashti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%